Life events predicting the first onset of adolescent direct self-injurious behavior - a prospective multicenter study - Kaess, Michael; Eppelmann, Lena; Brunner, Romuald; Parzer, Peter; Resch, Franz (Journal of adolescent health, 2020)
Purpose - Self-injurious behavior is a frequent phenomenon in adolescence. The present study prospectively examined life events as risk factors for the first onset of direct self-injurious behavior (D-SIB) in the Saving and Empowering Young Lives in Europe school-based multicenter sample. - Methods - Longitudinal assessments with an interval of 1 year were performed within a sample of 1,933 adolescents (51.47% females; mean age 14.84 ± .9 years) from 10 European countries and Israel. - Results - The number of life events during the past 6 months predicted the first onset of D-SIB in the following year. Gender neither predicted the onset of D-SIB nor moderated the association with life events. Moreover, analyses of individual events identified a range of mainly interpersonal events within both family and peer group as proximal risk factors for first episode D-SIB. - Conclusions - The results support the critical role of interpersonal life events in the development of D-SIB for both genders and refine the conceptualization of proximal risk factors in terms of accumulated stressors and interpersonal events.
Available online 31 October 2019
Gesehen am 21.02.2020